DINAMIKA KEPRIBADIAN PRESPEKTIF PSIKOLOGI ISLAM: TELAAH KRITIS PEMIKIRAN IBNU SINA - Gunnawan; Septiansyah, Moch. Agung Lukman (LP2M IAI Miftahul Ulum Pamekasan, 2022)
The character of each and every individual really has its own uniqueness, as indicated by the human limit itself, lined up with the Qur'an's bayan in regards to character. This article is a subjective examination utilizing library research. Library research is a progression of exercises with the strategies for gathering library information, perusing, and overseeing research materials. In light of the consequences of the review, Ibn Sina's complete name was Abu ali al Husain container Abdullah receptacle al Hasan canister Ali receptacle Ibn Sina, Ibn Sina was brought into the world around the fourth century H. As per Ibn Sina the spirit is equivalent to the Soul. As per him the spirit is the underlying flawlessness, in light of the fact that with it the creature is culminated so it turns into a genuine individual. The Qur'an gives high concordance to human regard which is named